Legal Protection of Brand Rights Holders for Brands Counterfeiting in E-Commerce in Indonesia - Gede Angga Prawirayuda; I Nyoman Putu Budiartha; Ni Luh Made Mahendrawati (Jurnal Hukum Prasada, 2020)
The most detrimental thing is the use of domain names on internet networks that often use company name, brand and services without permission from the brand owner. The position of the brand is very important in the world of advertising and marketing. That happens because consumers in choosing a product related to the reputation of a brand, based on a sense of trust in the experience in using products with that brand. Aside from being a differentiator of a product with other products, a brand is also a valuable and commercial asset that has moral rights and economic rights. This study aims to analyse the preventive and repressive legal protection of trademark rights holders in e-commerce transactions. This research was conducted using the normative legal research method. The results of this study indicate that the preventive legal protection of trademark rights holders in e-commerce transactions is to register the trademark. The emphasis on preventive protection in this research is related to guarantees of the exercise of rights for brand rights holders in e-commerce transactions. That the presence of the government by drafting the Electronic Commerce Act and conducting socialization related to the legal protection of the parties in e-commerce is expected to be able to provide legal certainty of legal protection. Repressive legal protection in resolving trademark disputes is expected to create a guarantee for the enforcement of the rights of registered trademark rights holders in e-commerce transactions. Settlement of trademark disputes in e-commerce transactions can be done in 2 (two) ways, namely litigation and non-litigation.